PENGARUH MODEL PEMBELAJARAN KOOPERATIF LEARNING TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP SISWA (Studi Kuasi Eksperimen pada Mata Pelajaran Ekonomi kelas X di SMA Negeri 27 Bandung) - Yudho Ramafrizal (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2017)
This study aimed to determine the differences in concept comprehension ability of student who received expository method with cooperative learning model type STAD (student Teams Achievment Division) on the subject of economy. The method used is a quasi-experimental method, the study subjects consisted of two classes of class X1 (control Group) and X2 (experiment group). Data was collected through observation and written test given to the student. Data processing is performed by t-test (paired-sample t-test) and the independent sample t-test using SPSS 21 application. Based on the result of the study showed that the model of cooperative learning type STAD can improve students’ ability to comprehension concept. Increased ability to comprehension concept student using cooperative learning type STAD model is higher than the increase in comprehension concept ability of student using expository teaching methods.